The Effectiveness of Human Resource Development Management in Efforts to Improve The Quality of Education in SD Negeri 90 Ogan Komering Ulu - Dauzar Dauzar; Happy Fitria; Alhadi Yan Putra (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the effectiveness of human resource development management to increase quality at SD Negeri 90 Ogan Komering Hulu (OKU). This research is a qualitative research with  qualitative descriptive approach. The data obtained were collected through observation, interview and documentation techniques. The results showed that the human resource development steps carried out at SD Negeri 90 OKU were carried out in 7 steps, namely compiling programs, determining needs, determining targets, determining programs, identifying learning principles, program implementation and evaluation of program implementation. Human resource management at SD Negeri 90 OKU, both in terms of quality improvement, implementation, supporting factors and the quality of education have been running optimally.